PENERAPAN PEMBELAJARAN PJOK BERBASIS BELAJAR MANDIRI DI TINGKAT SEKOLAH DASAR DI KOTA BINJAI - Alhumary, Farid M. (Indonesia Sport Journal, 2023)
The purpose of this research is to find out how the PJOK SDN Binjai City program includes an autonomous learning curriculum. This type of research is quantitative and descriptive. In this study, the total sample was fifteen people. The sample was two elementary school students in Binjai Kota Regency and all teachers of PJOK subjects who had attended seminars or training on the independent learning curriculum. SPSS 25 is used by researchers to test hypotheses. Based on research on the implementation of the autonomous curriculum in learning PJOK subjects in Binjai City, 37.5% of teachers rated it as good, and 62.5% rated it as good. The procedure is fair to excellent. In 62.5% of cases, students said everything went well.